School Readiness and Community-Based Early Childhood Development (ECD) Centres in Low-Income Communities: Examining The Case of Gugulethu, Western Cape Province, South Africa - Miriam Chikwanda; Amiena Bayat; Siphe Madyibi (Faculty of Teacher Training and Education, Universitas Terbuka, 2022)
A child must be exposed to early learning situations and assisted in developing the skills and ways of functioning to develop, thrive, and be ready for school. It is established that poor school readiness preparation (SRP) negatively impacts subsequent learning outcomes. A qualitative study was conducted in Gugulethu, a poor community in the Western Cape province in South Africa, to determine how Early Childhood Development centres in a poor community prepare children for schooling. The study involved a sample of 12 community-based ECD centres. Interviews and focus group discussions were conducted with direct role-players, including principals, practitioners, and ECD industry key informants. Data was enriched through direct observation of operations at each facility. The study found that all the community-based ECD centres struggle to provide quality SRP. Contributing factors include limited ECD practitioner training, education resources, infrastructure, and facility management. Because these conditions relate to poverty, they affect the SRP of most children in poorer communities, such as Gugulethu, who tend to only have access to under-resourced ECD centres. The study concludes that, given the appalling performance of South Africa’s basic education system, the government has to accept that improving its learning outcomes begins with vastly improving the SRP of children from birth